2000
DOI: 10.1086/312640
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Chandra X-Ray Observatory[/ITAL] Arcsecond Imaging of the Young, Oxygen-rich Supernova Remnant 1E 0102.2−7219

Abstract: We present observations of the young, oxygen-rich supernova remnant 1E 0102.2-7219 taken by the Chandra X-Ray Observatory during its orbital activation and checkout phase. The boundary of the blast-wave shock is clearly seen for the first time, allowing the diameter of the remnant and the mean blast-wave velocity to be determined accurately. The prominent X-ray bright ring of material may be the result of the reverse shock encountering ejecta; the radial variation of O vii versus O viii emission indicates an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 10 publications
12
94
1
1
Order By: Relevance
“…It is the brightest SNR in X-rays in the Small Magellanic Cloud (SMC). E0102 has been extensively imaged by Chandra (Gaetz et al 2000;Hughes et al 2000) and XMM-Newton (Sasaki et al 2001). Figures 1 and 2 show images of E0102 with the relevant spectral extraction regions for each of the instruments included in this analysis.…”
Section: The Snr 1e 01022-7219mentioning
confidence: 99%
See 2 more Smart Citations
“…It is the brightest SNR in X-rays in the Small Magellanic Cloud (SMC). E0102 has been extensively imaged by Chandra (Gaetz et al 2000;Hughes et al 2000) and XMM-Newton (Sasaki et al 2001). Figures 1 and 2 show images of E0102 with the relevant spectral extraction regions for each of the instruments included in this analysis.…”
Section: The Snr 1e 01022-7219mentioning
confidence: 99%
“…Since our objective is calibration, we decided against using any of the available plasma emission models for several reasons. First, the Chandra results on E0102 (Flanagan et al 2004;Gaetz et al 2000;Hughes et al 2000) have shown there are significant spectral variations within the SNR, implying that the plasma conditions are varying throughout the remnant. Since the other missions considered Suzaku XIS 6' 50.7" Fig.…”
Section: Construction Of the Spectral Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…E0102 is not obviously detected at 70 mm, although there is a small bump present in the low-level IR contours exactly at the remnant's position. The measured flux density of the whole rem- Gaetz et al (2000). The X-ray image was smoothed to match the resolution of the IR image.…”
Section: Observations and Data Processingmentioning
confidence: 99%
“…Additionally, the X-ray ejecta are observed in Cas A with a range of ionization states and densities (Lazendic et al 2006), these values have implications for the further plasma evolution of the features and we may be able to directly measure the plasma-state changes in future observations. (Figure 3, right-most) clearly shows the outer blast wave and bright inner rings of H-and He-like O and Ne emission (Gaetz et al 2000). A proper motion measurement in the X-ray was made using ROSAT, Einstein, and Chandra data (Hughes et al 2000b), giving 0.10 % ±0.025% yr −1 and the FS velocity in Table 2.…”
Section: Core-collapse X-ray Observationsmentioning
confidence: 99%